Thyroid Dysfunction in Mycosis Fungoides: Sonographic and Laboratory Insights - Dalia Halwag; Samar Mohamed Samy Gad; Eman M ElEryan; Hend Mostafa Ali Ali; Eman M Osman; Iman Mohamed Abdelmeniem (Dermatology Practical & Conceptual)
Introduction: Thyroid gland affection in mycosis fungoides has been rarely reported. It occurs as extracutaneous involvement, incidentally, as a second malignancy, or as a side effect of systemic retinoids.